Increasing prevalence of overweight and obesity among Tanzanian women of reproductive age intending to conceive: evidence from three Demographic Health Surveys, 2004-2016 - Amani I Kikula; Aline Semaan; Belinda Balandya; Naku K Makoko; Andrea B Pembe; José L Peñalvo; Lenka Beňová (Inishmore Laser Scientific Publishing Ltd, 2023)
# Background The prevalence of people who are overweight or obese is increasing globally, especially in low- and middle-income countries. High body mass index (BMI) among women of reproductive age is a risk factor for various adverse reproductive and pregnancy outcomes. This study aims to describe trends over time in the distribution of BMI among Tanzanian women of reproductive age intending to conceive between 2004/5 and 2015/16, and identify factors associated with high BMI. # Methods We used data on 20,819 women of reproductive age (15-49 years) intending to conceive who participated in the Tanzania Demographic and Health Surveys in 2004/5, 2010 and 2015/16. We estimated the prevalence of high BMI (being overweight \[≥25 to <30 kg/m^2^] and obesity \[≥30kg/m^2^) and trends in the prevalence of high BMI across the three surveys. Using survey-weighted multivariable logistic regression, we used the most recent 2015/16 survey data to identify factors associated with high BMI. # Results Median BMI increased from 21.7kg/m^2^ (inter-quartile range, IQR=19.9-24.1 kg/m^2^) in 2004/5 to 22.0 kg/m^2^ (IQR=20.0-24.8 kg/m^2^) in 2010 to 22.7 kg/m^2^ (IQR=20.4-26.0 kg/m^2^) in 2015/16. The prevalence of overweight women increased from 11.1% in 2004/5 to 15.8% in 2015 (P <0.001). The prevalence of obesity increased from 3.1% in 2004/5 to 8.0% in 2015/16 (P<0.001). Women in the highest wealth quintile had higher odds (adjusted odds ratio, aOR= 4.5; 95%CI 3.4-6.3, P<0.001) of high BMI than women in the lowest quintile. The odds of high BMI were about four times greater (aOR=3.9; 95%CI=2.9-5.4, P<0.001) for women 40-44 years compared to 20-24-year-olds. Women in the high-paying occupations had greater odds of high BMI than those working in agriculture (aOR=1.5; 95% CI=1.1-2.2, P=0.002). Women residing in the Southern zone had 1.9 (95%CI=1.5-2.5, P<0.001) greater odds of high BMI than Lake zone residents. # Conclusions In Tanzania, high BMI affects almost 1 in 4 women of reproductive age who intend to conceive. This contributes to the burden of poor maternal and reproductive health outcomes. We recommend developing and implementing health-system strategies for addressing high BMI, tailored to the modifiable risk factors identified among women of reproductive age.